Evaluasi Pelaksanaan Penilaian Autentik dalam Kurikulum Merdeka pada Pembelajaran IPAS di MI Al-Islamiyah Bebidas: Evaluation of the Implementation of Authentic Assessment in the Merdeka Curriculum for IPAS Learning at MI Al-Islamiyah Bebidas - Lisnawati (Lembaga Bale Literasi, 2025)
The Merdeka Curriculum places authentic assessment as the primary instrument for evaluating students' learning outcomes holistically, encompassing the cognitive, affective, and psychomotor domains. This study aims to evaluate the implementation of authentic assessment in Natural and Social Sciences (IPAS) learning, identify supporting and inhibiting factors, and analyze its impact at MI Al-Islamiyah Bebidas. The method used is descriptive qualitative with the CIPP (Context, Input, Process, Product) model evaluation design. Data were obtained through observation, interviews with the madrasah principal, IPAS teachers of grades IV–V, students, and documentation, then analyzed using source triangulation techniques. The results indicate that the implementation of authentic assessment has not been optimal because teachers rely more on written and oral tests, while project-based and portfolio assessments have not been applied consistently. Obstacles include limited teacher competence, supporting facilities, time management, and student discipline. Meanwhile, supporting factors include teachers' awareness of the urgency of authentic assessment and students' enthusiasm for interactive learning. This study concludes that authentic assessment has a positive impact on students' motivation, engagement, and critical thinking skills, although its implementation has not been fully comprehensive.